Tinjauan Yuridis Terhadap Kopi Dapat Dikatakan Doping Jika Melebihi Takaran Yang Telah Ditentukan (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Coffee has become a beverage not only refreshing but also an energy drink that dominates the global beverage market with its unparalleled appeal. coffee opens up many positive opportunities in sports. Dope was first introduced in 1889. The ergogenic dose of caffeine is about 250-500 mg per day (three cups of coffee or six to eight soft drinks). Most athletes consume caffeine in pill form. Caffeine can be considered doping if it exceeds the set maximum limit. That is why a controlling body is needed to control this issue, thus WADA was born. WADA is an independent international agency that was established in 1999 to also control world anti-doping standards. This private sector was created after a historic event in the world. of sports when it was discovered that a cyclist had used doping at the 1998 Summer Olympics